TALEN-based editing of TFIIAy5 changes rice response to Xanthomonas oryzae pv. Oryzae - Han, Jin (Sci Rep, 2020)
The xa5 gene encodes a basal transcription factor (TFIIAγ) protein with wide spectrum resistance to bacterial blight caused by Xanthomonas oryzae pv. Oryzae (Xoo) in rice. It was only found in a few rice ecotypes, and the recessive characteristics limited its application in breeding. Here, we employed a TALEN-based technique to edit its dominant allelic TFIIAγ5 and obtained many mutant TFIIAγ5 genes. Most of them reduced rice susceptibility to varying degrees when the plants were challenged with the Xoo. In particular, the knocked-out TFIIAγ5 can reduce the rice susceptibility significantly, although it cannot reach the xa5-mediated resistance level, indicating TFIIAγ5 is a major component involved in disease susceptibility. In addition, the mutant encoding the protein with deletion of the 32nd amino acid or amino acid insertion between 32nd and 33rd site confers rice with the similar resistance to that of the knocked-out TFIIAγ5. Thus, the amino acids around 32nd site are also the important action sites of TFIIAγ5 besides the 39th amino acid previously reported. Moreover, the integration of xa5 into TFIIAγ5-knockout plants conferred them with a similar resistance as IRBB5, the rice variety containing the homozygous xa5 gene. Thus, TFIIAγ5 was not simply regarded as a resistant or a susceptible locus, as the substitution of amino acids might shift its functions.